Drosophila Gtsf1 is an essential component of the Piwi-mediated transcriptional silencing complex. - Dönertas, D.; Sienski, G.; Brennecke, J. (Genes & Development, 2013)
The PIWI-interacting RNA (piRNA) pathway is a small RNA silencing system that keeps selfish genetic elements such as transposons under control in animal gonads. Several lines of evidence indicate that nuclear PIWI family proteins guide transcriptional silencing of their targets, yet the composition of the underlying silencing complex is unknown. Here we demonstrate that the double CHHC zinc finger protein gametocyte-specific factor 1 (Gtsf1) is an essential factor for Piwi-mediated transcriptional repression in Drosophila. Cells lacking Gtsf1 contain nuclear Piwi loaded with piRNAs, yet Piwi's silencing capacity is ablated. Gtsf1 interacts directly with a small subpool of nuclear Piwi, and loss of Gtsf1 phenocopies loss of Piwi in terms of deregulation of transposons, loss of H3K9 trimethylation (H3K9me3) marks at euchromatic transposon insertions, and deregulation of genes in proximity to repressed transposons. We propose that only a small fraction of nuclear Piwi is actively engaged in target silencing and that Gtsf1 is an essential component of the underlying Piwi-centered silencing complex.